A STUDY ON THE LISTENING ABILITY OF THE FOURTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM FKIP UNIVERSITAS RIAU IN COMPREHENDING ACADEMIC TALKS - Ummi Zurrahmi; Fadly Azhar; Fakhri Ras (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aim of this study is to find out the listening ability of the fourth semester students of English Study Program FKIP Universitas Riau in comprehending academic talks. The population of this research were all of the fourth semester students which consisted of 89 students. There were 48 students who participated in this study. The instrument was a test adapted from TOEFL Test (Listening Comprehension Part C). The test consisted of 8 academic talks and had 4 questions for each talk. Before the test was administered, the test was tried out to find out the difficulty level and the reliability of the test. To analyze the data, the mean score of the students was calculated and the level of ability was identified by using the classification of ability level by Harris (1974). The result showed that the ability of the fourth semester students of English Study Program FKIP Universitas Riau in comprehending academic talks was at Good level with mean score 61.2. Therefore, it can be concluded that most of the students were able to comprehend talks related to academic situations. However, the students are suggested to practice listening to various aural inputs especially academic talks to improve the ability in listening due to the poorness of their listening ability.Key Words: Listening Ability, Listening Comprehension, Academic Talks